2017
DOI: 10.1177/1076029616687849
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Interaction With Hepatic Cytochrome P-450 Enzyme-Inducing Anticonvulsants

Abstract: Initiation of cytochrome P-450 (CYP)-inducing anticonvulsant medications during warfarin therapy may decrease anticoagulant effect and necessitate frequent warfarin dose adjustments to maintain therapeutic response measured by the international normalized ratio (INR). Clinical information regarding interactions between warfarin and these medications is limited. This study investigated warfarin dose and INR response following CYP-inducing anticonvulsant initiation among chronic warfarin users. This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…[34][35][36][37] On the other hand, some previously documented DDIs were not associated with statistically significantly elevated RR or ratio of RRs in our study, for example, carbamazepine (RR=1.07, 95% CI: 0.88-1.30, ratio of RRs=0.82, 95% CI: 0.56-1.21), phenytoin (RR=0.90, 95% CI: 0.80-1.00, ratio of RRs=1.19, 95% CI: 0.90-1.58), and phenobarbital (RR=0.82, 95% CI: 0.63-1.08, ratio of RRs=1.37, 95% CI: 0.69-2.75). 38,39 This may be due to lack of dose adjustment as patients may be told to skip doses when they initiated these precipitant drugs, potential misclassification for days on warfarin, and/or insufficient power. Our approach was designed to screen a large number of potentially interacting precipitant drugs in a high-throughput fashion and generate new DDI hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] On the other hand, some previously documented DDIs were not associated with statistically significantly elevated RR or ratio of RRs in our study, for example, carbamazepine (RR=1.07, 95% CI: 0.88-1.30, ratio of RRs=0.82, 95% CI: 0.56-1.21), phenytoin (RR=0.90, 95% CI: 0.80-1.00, ratio of RRs=1.19, 95% CI: 0.90-1.58), and phenobarbital (RR=0.82, 95% CI: 0.63-1.08, ratio of RRs=1.37, 95% CI: 0.69-2.75). 38,39 This may be due to lack of dose adjustment as patients may be told to skip doses when they initiated these precipitant drugs, potential misclassification for days on warfarin, and/or insufficient power. Our approach was designed to screen a large number of potentially interacting precipitant drugs in a high-throughput fashion and generate new DDI hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 8 ] Moreover, warfarin is stereo selectively metabolized by hepatic cytochrome P-450 microsomal enzymes to inactive hydroxylated metabolites and by reductases to reduced metabolites with minimal anticoagulant activity. [ 9 ] Thus, hepatic impairment can potentiate the response to warfarin through decreased metabolism of warfarin. Several retrospective studies revealed that patients with liver disease were significantly more likely to have a high INR when taking warfarin, and worsening liver dysfunction was found to be strongly associated with bleeding episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Gout is the most common form of inflammatory arthritis (Fields, 2019), and recently, it has been recognized as a serious disease that causes functional disability and has negative economic consequences for individuals and communities. This disease can affect joints in the body, not only the big toe, and in some cases it even mimics polyarthritis (Clark et al., 2018). Hyperuricemia has been identified as the most important risk factor for gout, and the successful management of this disease requires a sustained serum uric acid (sUA) level of <6.0 mg/dl (FitzGerald et al., 2020).…”
Section: Introductionmentioning
confidence: 99%